Pemanfaatan Gliserol Dari Produk Samping Biodiesel Menjadi Triacetin Melalui Proses Esterifikasi Menggunakan Katalis Zeolit Alam - Rizki, Juliana; Helwani, Zuchra; Rionaldo, Hari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Glycerol by-product of biodiesel through transesterification reaction is currently not fully utilized as raw materials or as chemical products. Crude glycerol can be purified to be processed into more useful products. Through conversion into triacetin with the esterification process using acetic acid and solid catalyst in the form of natural zeolite. Triacetin can be used for food and non-food. The objective of this study was to study the effect of catalyst loading natural zeolite and temperature on glycerol conversion on triacetin production process. The experiments were carried in batch process with time of reaction 4 hours were optimum for glycerol conversion, the molar ratio of glycerol to acetic acid 1 : 7 and size of catalyst -100 mesh and +150 mesh with variation of reaction temperature (90, 100, and 110 oC) and catalyst concentration (1%, 3%, and 5%-w). The results of the qualitative analysis by means of Fourier Transform Infrared Spectroscopy confirmed there is triacetin as product. Increasing of temperature reaction increased of glycerol conversion. But increasing of catalyst loading not increased of glycerol conversion. The glycerol conversion was 96,49%, where obtained using the reaction condition: temperature 110 oC and catalyst of natural zeolite was 3% (w/w) acetic acid based. Keywords: glycerol, esterification, zeolites, triacetin